Advancements in Proton Therapy for Cancer Treatment: Benefits and Challenges - Obaeed, Laheeb Kareem; Muhamad, Bariq Ali Eabd Eawn; Rasheer, Anwar Mohammed Abood; Hussien, Falah Ghayib; Takhakh, Karar Sajid Rahman (American Journal of Botany and Bioengineering, 2024)
Raised in 2016, the proton treatment center at the Washington University Medical Center in St Louis, Missouri, houses a 230-ton superconducting cyclotron, capable of accelerating proton particles at energies up to 250 MeV (megaelectronvolts). The protons then deliver a radiation dose to a patient as determined by a team of physicians, physicists, and dosimetrists. The machine is able to deliver spot scanning irradiation of protons, in addition to a passive scatter delivery. Clinical examinations and imaging are done in-house with CT, MRI, and PET/CT, and it scans the patient in the treatment position. During radiation therapy, a patient is aligned on the treatment table with respect to the room coordinate system and the treatment plan. A subsequent target ionization chamber (ICs) readout instrument can monitor, in-vivo, the total delivered dose to compare with the treatment plan. Furthermore, it can function as an interlock device in a treatment plan to halt a treatment if it is deemed unsafe. After treatment, a post-ICs, Gafchromic EBT3 film was placed in the same scan bed to measure the out-of-beam dose from the earlier treatment [1]. During this single-film approach readout, the film was scanned in the film’s scan orientation before and after treatment. Crop study has been conducted to ensure that the area of interest was not outside of the beam region or in the steep dose gradient region.